2016
DOI: 10.1016/j.cub.2015.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Signal Use by Octopuses in Agonistic Interactions

Abstract: Cephalopods show behavioral parallels to birds and mammals despite considerable evolutionary distance [1, 2]. Many cephalopods produce complex body patterns and visual signals, documented especially in cuttlefish and squid, where they are used both in camouflage and a range of interspecific interactions [1, 3-5]. Octopuses, in contrast, are usually seen as solitary and asocial [6, 7]; their body patterns and color changes have primarily been interpreted as camouflage and anti-predator tactics [8-12], though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…For example, it has been reported that the squid Loligo plei display specific body patterns in order to threaten their opponents during male-male fighting behavior (DiMarco and . It has also been found that a dominant octopus shows dark body patterns in order to threaten their subordinates (Scheel et al, 2016). In addition, it has been demonstrated that female mature squids show bright stripes on the dorsal mantle, similar to the bright white testis of adult males, which is indicative of female choice (avoidance of mating) during courtship behavior (DeMartini et al, 2013).…”
Section: Visual Signals Determine the Behavioral Outcome During Squidmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it has been reported that the squid Loligo plei display specific body patterns in order to threaten their opponents during male-male fighting behavior (DiMarco and . It has also been found that a dominant octopus shows dark body patterns in order to threaten their subordinates (Scheel et al, 2016). In addition, it has been demonstrated that female mature squids show bright stripes on the dorsal mantle, similar to the bright white testis of adult males, which is indicative of female choice (avoidance of mating) during courtship behavior (DeMartini et al, 2013).…”
Section: Visual Signals Determine the Behavioral Outcome During Squidmentioning
confidence: 99%
“…In addition, it has been observed that male squids showed agonistic behavior and fight for the possession of the female during reproductive interactions (Moynihan and Rodaniche, 1982;Jantzen and Havenhand, 2003b). Cephalopods are highly visual animals and they communicate through dynamic body patterning, thus it is likely that visual communication between males and females during courtship behaviors, as well as between different males during agonistic behavior, may determine their mating strategies (Hanlon et al, , 2002(Hanlon et al, , 2005Jantzen and Havenhand, 2003a,b;Naud et al, 2004Naud et al, , 2016Iwata et al, 2005;Wada et al, 2005;Huffard et al, 2008;Buresch et al, 2009;Scheel et al, 2016).…”
Section: Visual Signals Determine the Behavioral Outcome During Squidmentioning
confidence: 99%
See 2 more Smart Citations
“…We first applied the extended model (13) to the case of mixed sexs with equal we find that f = 0 and m = 1 (n f 0 = 1/11,n m 0 = 0). The number of configurations is 346 then ⌦ = 9 3 8 3 = 4704.…”
mentioning
confidence: 99%